1995
DOI: 10.1182/blood.v85.11.3313.bloodjournal85113313
|View full text |Cite
|
Sign up to set email alerts
|

Expression of adhesion molecules on CD34+ cells: CD34+ L-selectin+ cells predict a rapid platelet recovery after peripheral blood stem cell transplantation

Abstract: Adhesion molecules play a role in the migration of hematopoietic progenitor cells and regulation of hematopoiesis. To study whether the mobilization process is associated with changes in expression of adhesion molecules, the expression of CD31, CD44, L-selectin, sialyl Lewisx, beta 1 integrins very late antigen 4 (VLA-4) and VLA-5, and beta 2 integrins lymphocyte function-associated 1 and Mac-1 was measured on either bone marrow (BM) CD34+ cells or on peripheral blood CD34+ cells mobilized with a combination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
49
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(57 citation statements)
references
References 30 publications
7
49
1
Order By: Relevance
“…Indeed, CD62L expression has been correlated to speed of hematopoietic recovery 30 and in particular with PLT recovery. 31 In this regard, the lower migration toward an SDF-1a gradient of the CD62L-population we observed seems compatible with previous reports. The lower number of CD62L-expressing cells derived from the ECT pathway might in this regard explain why fewer cells from the ECT pathway are able to migrate toward or within the marrow.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, CD62L expression has been correlated to speed of hematopoietic recovery 30 and in particular with PLT recovery. 31 In this regard, the lower migration toward an SDF-1a gradient of the CD62L-population we observed seems compatible with previous reports. The lower number of CD62L-expressing cells derived from the ECT pathway might in this regard explain why fewer cells from the ECT pathway are able to migrate toward or within the marrow.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, cryopreservation may effect the homing potential of stem cells. It has been shown that the expression of certain adhesion molecules and the in vitro migratory capacity of CD34 + cells are correlated with haematological recovery (Dercksen et al, 1995;Watanabe et al, 1998;Voermans et al, 2001). Comparison of adhesion molecule expression on WB CD34 + cells after 3 d of refrigerated storage with cryopreserved PBSC CD34 + cells revealed a 50% loss of l-selectin expression on the non-apoptotic CD34 + cells of the cryopreserved PBSC (De Boer et al, 2002b).…”
Section: Discussionmentioning
confidence: 99%
“…We were further interested whether cell cycle progression is linked to the expression of adhesion molecules. Antigens of the β 1 -integrin (CD49b, CD49d, CD49e), the β 2 -integrin (CD18), the selectin (CD62L), and the immunoglobulin (CD58) family that had previously been found on normal or leukemic hematopoietic progenitor cells [19][20][21] were included in this matchedpair steady-state BM and mobilized PB analysis. The highest proportion of CD34 + cells expressed CD49d, followed by CD49e and CD49b regarding β 1 -integrins (Table 3).…”
Section: Expression Of Adhesion Molecules and Correlation With Cell Cmentioning
confidence: 99%
“…In previous experiments, we and others found a significantly greater fluorescence intensity of the adhesion molecule CD49d and the leukocyte function associated molecule-1 (LFA-1) complex which consists of the αL/β2 (CD11a/CD18) chains on BM CD34 + cells than with mobilized PBPC [17,18]. In this analysis also, CD49b, CD49e, CD58 (LFA-3), and CD62L (L-Selectin), which were all reported on CD34 + cells, were included [19][20][21]. Leukapheresis product samples were obtained from 14 patients with hematological malignancies and solid tumors following G-CSF-supported cytotoxic chemotherapy and were compared with BM cells obtained prior to mobilization from these patients with regard to cell biological and immunological progenitor cell subsets as well as cell cycle state.…”
Section: Introductionmentioning
confidence: 99%